Implementasi Metode Pembelajaran Aktif Dalam Pendidikan Ekonomi - Telaumbanua, Sozui Metafati (CV. SINAR HOWUHOWU, 2026)
Economics learning is often perceived as theoretical and abstract by students. This journal discusses the implementation of active learning methods as a solution to increase student engagement and understanding of economic concepts. Using a descriptive-qualitative approach, this study evaluates various techniques such as Problem-Based Learning (PBL), market simulations, and case studies. The results indicate that active learning methods not only improve cognitive scores but also hone critical thinking skills and financial literacy, which are necessary for navigating the dynamics of the global economy.